Effect of peri-operative milrinone on pulmonary artery pressure in patients undergoing mitral valve replacement - Dolapoğlu, Ahmet; Avcı, Eyüp (Journal of Surgery and Medicine, 2019)
Aim: Increased pulmonary artery pressure is associated with higher surgical risk in patients undergoing mitral valve replacement. The aim of this study was to investigate the effect of milrinone on the pulmonary artery pressures of patients with mitral valve disease (stenosis or regurgitation) who underwent mitral valve replacement surgery. Methods: In this case-control study, 48 patients with mitral valve disease who underwent mitral valve replacement surgery were included. The patients were divided into a control group of 30, who were not administered milrinone, and a study group of 18 who received milrinone perioperatively. Systolic pulmonary artery pressures (SPAP), left ventricle ejection fractions (LVEF) and the following postoperative outcomes were recorded: low cardiac output syndrome, stroke, renal failure, bleeding, ventricular arrhythmia and mortality occurring within 30 days of surgery either in or out of the hospital. Results: In the study group, preoperative LVEFs and postoperative low cardiac output syndrome were lower (72.0 (6.1) vs 62.5(8.4) P<0.001 and P=0.007, respectively), SPAPs were higher (45.50 (7.0) vs 55.06 (5.5), P<0.001), and length of stay in intensive care unit was significantly shorter (4.7 (2.2) vs 3.2 (0.5), P=0.008). Also, reduction in both postoperative SPAP and 30-day SPAP were significantly higher [-11.40(-13.25-(-8.63)) vs -4.42(-5.89-(-2.80)), P<0.001; -13.6(-15.6-(-9.75)) vs -5.56 (-7.20-(-3.30)), P<0.001, respectively]. Conclusion: We found that using perioperative milrinone reduces the systolic pulmonary artery pressure and lowers the rate of low cardiac output syndrome. Milrinone can be used as an effective therapy to reduce to pulmonary pressure in patients with pulmonary hypertension undergoing mitral valve replacement surgery.